PROSES MANUFAKTUR UNTUK PEMBUATAN PART SPOILER PESAWAT - Hibatullah, Fauzi; A. Sofwan F Alqap; Helmizar (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2023)
Manufacture is an activity or process to change the form of material from raw into semi or finished goods. The process begins with designing the product, determining the specifications of the material from which the product is made. A series of manufacturing processes may include cutting, forming, thermal treating, inspection, and finishing. Inspection duties are of the Quality Control section tasks. These duties include visual inspection and measurement that takes place before, during and after the production process. CNC machines that are operated for the cutting processes still use memory in the form of punched paper as a medium for transferring G and M codes to the control system. There are two programming methods in CNC machines, namely incremental method and absolute one. The first is where the reference point is always changing, i.e. the last point is to be used as a new reference for the next. The second is where the reference point is fixed, i.e. the first position is used as a reference for all steps. Spoilers are panels mounted on the upper surface of the wing that, when extended, both increase drag and decrease lift by disrupting the airflow over the wing. Manufacturing steps of the spoiler actuator are material verification, turning processes, removing burs, precipitation hardening, hardness checking, turning for surface finishing, grinding, honing, hole surface finishing, flaw inspection, and packing